Toxoplasma gondii in African Wildlife: A Systematic Review - Refilwe Philadelphia Bokaba; Veronique Dermauw; Darshana Morar-Leather; Pierre Dorny; Luis Neves (Pathogens, 2022)
Toxoplasma gondii (T. gondii) is a protozoan parasite, which infects a wide variety of mammals and bird species globally. In large parts of the world, this parasite is relatively well documented in wildlife species, however, this topic is poorly documented in Africa. The current review systematically explores the presence and distribution of T. gondii in African wildlife species through a key word search in PubMed, Web of Science and CAB Direct. A total of 66 records were identified and included in the qualitative analysis, of which 19 records were retained for the quantitative synthesis. The presence of T. gondii was reported in a wide range of wildlife species, found in twelve countries, spread over the African continent. The retained records report a prevalence range of 6–100% in herbivores, 8–100% in omnivores and 14–100% in carnivores. In wild felines (cheetahs, leopards, and lions) a prevalence range of 33–100% was found. Reports from South Africa, and on the presence of T. gondii in lion were most common. Overall, the results indicate the scarcity of information on T. gondii in Africa and its circulation in wildlife. The lack of knowledge on the parasite in Africa, especially in areas at the human-livestock-wildlife interface, prevents us from understanding how prevalent it is on the continent, what strains are circulating in wildlife and what the most common routes of transmission are in the different habitats in Africa.